Phase synchronization analysis of EEG functional connectivity in Parkinson’s disease - Rajagopal, Karthikeyan; Naseri, Nafise; Parastesh, Fatemeh; Ghassemi, Farnaz; Jafari, Sajad (Journal of theoretical biology, 2025)
[Display omitted] •PD patients show weaker delta band connectivity during motor tasks vs. controls.•Significant network connectivity changes in PD are noted during motor tasks.•Graph metrics reveal altered clustering and path length in PD vs. controls.•PD shows reduced global efficiency in the delta band during motor activities.•Increased small-worldness indicates altered brain network topology in PD. There is a growing need for research on Parkinson’s disease (PD), a neurological condition that often affects the elderly. By examining brain network connectivity, researchers are able to discover how different brain regions interact during various cognitive and behavioral tasks. They can also understand how changes in nonlinear connections may be linked to neurological and mental illnesses. In this paper, the synchrony levels of 59 EEG channels from 26 Parkinson’s patients and 13 healthy subjects is examined by utilizing Phase-Lag Index (PLI) during a motor task and resting-state conditions. Examining different EEG frequency bands shows that whole-brain synchronization in the delta band is significantly lower in PD patients compared to healthy subjects during the task. PD patients also exhibit a lower clustering coefficient and a higher shortest path length in this band during the task, which shows the higher small-worldness in Parkinson’s patients compared to healthy individuals. Moreover, the global efficiency in the delta band is significantly reduced in PD patients during the task. An analysis of local efficiency shows that PD and control groups differ in 57 channels. These results reveal that Parkinson’s patients appear to have considerable pathological abnormalities in their delta band connectivity and its characteristic features.